DIGITAL MARKETING STRATEGY: THE EFFECTIVENESS OF SOCIAL MEDIA IN ATTRACTING NEW CUSTOMERS - Silvia Ekasari; H. MR. Ulung Sembiring; Eka Budi Yulianti (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to evaluate the effectiveness of social media in attracting new customers as part of a digital marketing strategy. Data was collected through a literature review on the theme of social media platforms used by companies. Results show that social media has significant advantages in reaching a wide and diverse audience, enabling direct interactions that encourage customer trust, as well as providing in-depth analytical tools to measure campaign success. The findings emphasise the importance of social media integration in a company's marketing strategy to increase visibility, engagement and conversion of potential customers. The conclusion of this study underlines that investing in social media marketing is a strategic move that can provide long-term benefits for companies.